Membangun Network Video Recorder (NVR) MenggunakanSet Top Box (STB) Pada Rusunawa Poltesa Berbasis Wireless - Yudistira; Theresia Widji Astuti; Muhammad Usman; Ellys Mey Sundari; Fiqih Akbari (Julia: Jurnal Ilmu Komputer An Nuur, 2026)
This research proposes an innovative solution for recording and storing surveillance video data in the parking environment of Rusunawa Poltesa using a Set Top Box (STB)-based Network Video Recorder (NVR) with Armbian Linux operating system. STBs, typically used for television signal reception, are adapted into intelligent devices to efficiently control and manage surveillance cameras (IP Camera) at a lower cost compared to conventional NVRs. The use of wireless technology increases the flexibility of camera placement without the limitations of cables, simplifies installation, and allows for the adjustment of camera positions according to surveillance needs. The STB-based NVR implementation uses the open-source Shinobi Community Edition (Shinobi CE) software written in Node.js, enabling video recording from IP cameras in H.264 and H.265 formats. This research aims to find an integrated and innovative solution to improve the surveillance system in Rusunawa Poltesa in a modern, efficient, and cost-effective manner. The research results show that the STB-based NVR system can record video at frame rates up to 15 FPS at HD resolution and 5 FPS at SD resolution, with memory consumption of approximately 4.02 MB per minute for HD resolution (1920x1080) and 1.98 MB per minute for SD resolution (1280x720).